2015
DOI: 10.4236/fns.2015.616156
|View full text |Cite
|
Sign up to set email alerts
|

Technological, Sensorial and Nutritional Meat Quality Traits from Pig Fed with Conventional and Unconventional Diets

Abstract: The aim of the study was to evaluate the impact of unconventional food resources on the quality of pig meat. 90 pigs of which 20 were slaughtered at 180 days old for meat quality evaluation. It came out from the study that the highest L* and b* were obtained in A0 commercial feed, while the highest a* was recorded in A3 (P < 0.05). From 45 minutes to 24 h post-mortem, the highest pork hue value was recorded in A2, whereas the highest chromaticity was found in A0. The pH 45 and pH 24 of Mld (Muscle Longissimus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The effect of vegetable oil supplementation in the pigs’ diet may affect the quality and nutritive value of pork meat as well as its content of bioactive compounds [ 8 , 11 , 34 ]. Indeed, in this study, the kind of olive oil used for pig feeding influenced the quality of fresh meat and capocollo dry-cured meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of vegetable oil supplementation in the pigs’ diet may affect the quality and nutritive value of pork meat as well as its content of bioactive compounds [ 8 , 11 , 34 ]. Indeed, in this study, the kind of olive oil used for pig feeding influenced the quality of fresh meat and capocollo dry-cured meat.…”
Section: Discussionmentioning
confidence: 99%
“…In monogastric animals, the diet is the main factor able to affect the quality of meat with regard to fat composition [ 8 , 9 ]. Several authors have reported that the dietary fat source influences the lipid profile of muscle and subcutaneous fat in pork, thus affecting its nutritional and sensorial quality and suitability for technological processing [ 8 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%